Perancangan Aplikasi Deteksi Kemiripan Dokumen Teks Menggunakan Algoritma Shingling - Irwan Saputra Simanullang (STMIK Budi Darma, 2020)
Detection of similarity in text documents is needed to avoid the accumulation of information in a database or file system, one way to find out plagiarism between two documents by detecting the similarity of two documents to be compared to detect plagiarism, the Shingling Algorithm is an algorithm used for near-duplicate document search processes. Shingling's algorithm is implemented to detect similarities in text documents. The ease of copying information from one document to another is one of the effects of advances in information technology. And this leads to unwanted plagiarism, so that the document detection process can be minimized properly. In this study, the test results show that the application created can detect the similarity of text documents that have gone through various manipulations, namely scaling (enlarge / reduce), rotation, cropping (partially cut), and manipulating documents.